# Solve the problem ( Show your work )2x + 10 =- 4x – 9

## Answers

-3(b + 9) = -9

First, divide both sides by -3. / Your problem should look like: b + 9 = [tex]\frac{-9}{-3}[/tex]

Second, simplify [tex]\frac{9}{-3}[/tex] to [tex]\frac{9}{3}[/tex] / Your problem should look like: b + 9 = [tex]\frac{9}{3}[/tex]

Third, simplify [tex]\frac{9}{3}[/tex] to 3. / Your problem should look like: b + 9 = 3

Fourth, subtract 9 from both sides. / Your problem should look like: b = 3 - 9

Fifth, simplify 3 - 9 to get -6. / Your problem should look like: b = -6

b = -6

-3(b + 9) = -9

First, divide both sides by -3. / Your problem should look like: b + 9 = [tex]\frac{-9}{-3}[/tex]

Second, simplify [tex]\frac{9}{-3}[/tex] to [tex]\frac{9}{3}[/tex] / Your problem should look like: b + 9 = [tex]\frac{9}{3}[/tex]

Third, simplify [tex]\frac{9}{3}[/tex] to 3. / Your problem should look like: b + 9 = 3

Fourth, subtract 9 from both sides. / Your problem should look like: b = 3 - 9

Fifth, simplify 3 - 9 to get -6. / Your problem should look like: b = -6

b = -6

x = -19/6

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

Brackets Parenthesis Exponents Multiplication Division Addition Subtraction Left to RightEquality Properties

Step-by-step explanation:

Step 1: Define Equation

2x + 10 = -4x - 9

Step 2: Solve for x

Add 4x on both sides: 6x + 10 = -9Subtract 10 on both sides: 6x = -19Divide 6 on both sides: x = -19/6Step 3: Check

Plug in x into the original equation to verify it's a solution.

Substitute in x: 2(-19/6) + 10 = -4(-19/6) - 9Multiply: -19/3 + 10 = 38/3 - 9Add/Subtract: 11/3 = 11/3Here we see that 11/3 does indeed equal 11/3.

∴ x = -19/6 is the solution to the equation.